Visualizing Mortality Dynamics in the Lexis Diagram - Rau, Roland (The Springer Series on Demographic Methods and Population Analysis,, 2018)
This book visualizes mortality dynamics in the Lexis diagram. While the standard approach of plotting death rates is also covered, the focus in this book is on the depiction of rates of mortality improvement over age and time. This rather novel approach offers a more intuitive understanding of the underlying dynamics, enabling readers to better understand whether period- or cohort-effects were instrumental for the development of mortality in a particular country. Besides maps for single countries, the book includes maps on the dynamics of selected causes of death in the United States, such as cardiovascular diseases or lung cancer. The book also features maps for age-specific contributions to the change in life expectancy, for cancer survival and for seasonality in mortality for selected causes of death in the United States. The book is accompanied by instructions on how to use the freely available R Software to produce these types of surface maps. Readers are encouraged to use the presented tools to visualize other demographic data or any event that can be measured by age and calendar time, allowing them to adapt the methods to their respective research interests. The intended audience is anyone who is interested in visualizing data by age and calendar time; no specialist knowledge is required. This book is open access under a CC BY license. .